Quantifying uncertainty in the estimation of probability distributions - H.T. Banks; Jimena L. Davis (Mathematical Biosciences and Engineering)
We consider ordinary least squares parameter estimation problemswhere the unknown parameters to be estimated are probabilitydistributions. A computational framework for quantification ofuncertainty (e.g., standard errors) associated with the estimatedparameters is given and sample numerical findings are presented.